Do managers really care about shareholders’ expectations? Evidence on dividend smoothing on Latin American emerging stock markets - Mosionek-Schweda, Magdalena; Mrzygłód, Urszula; Nowak, Sabina (Czy menedżerowie spółek starają się uwzględniać oczekiwania akcjonariuszy? Analiza zjawiska wygładzania dywidend na wybranych giełdowych rynkach Ameryki Łacińskiej, 2017)
The main goal of the paper is to examine dividend smoothing behaviour amongcompanies listed on the stock markets in Brazil, Chile, Colombia, Mexico and Peru in theperiod of 1994-2015. The research sample consisted of 227 companies and 4968 observations.On the basis of Lintner’s dividend partial adjustment model, we calculated the speed of dividendadjustment (SOA) in response to the change in earnings. We found many companies with lowSOA values, which on the grounds of the classic Linter’s approach implies the existence ofdividend smoothing. However, the obtained average SOA values varied in four out of fiveanalyzed stock markets from 0.731 for Chile to 0.914 for Brazil.This means that on selectedemerging stock markets of Latin America – except Peru – the dividend smoothing has notbeen confirmed. Moreover, the obtained SOA levels varied among the selected stock markets,which implies that the differences in the speed of dividend adjustment may be driven by eithernational or stock markets characteristics
Ekonometria = Econometrics, 2017, Nr 2 (56), s. 67-91
Keywords: payout policy; dividend smoothing; emerging markets; Latin American stockmarkets; polityka dywidendy; wygładzanie dywidend; rynki wschodzące; giełdy papierów wartościowych państw Ameryki Łacińskiej